2023
DOI: 10.1002/ctm2.1156
|View full text |Cite
|
Sign up to set email alerts
|

Exosome‐derived circTFDP2 promotes prostate cancer progression by preventing PARP1 from caspase‐3‐dependent cleavage

Abstract: Background Circular RNAs (circRNAs) have been reported to play a significant role in tumorigenesis. However, the detailed function of circRNA in prostate cancer (PCa) is still largely unknown. Methods We quantified circTFDP2 expression in PCa tissues and adjacent normal tissues using quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR). Colony formation, Cell Counting Kit‐8 (CCK‐8), flow cytometry, transwell, and in vivo progression and metastasis assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…In addition, it was reported that exosomal circRNA HIPK3 knockdown inhibited cell proliferation and metastasis in prostate cancer by regulating miR-212/BMI-1 pathway [58]. circ0081234 was inhibited is able to reduce prostate cancer tumor growth and metastasis via the miR-1/ MAP 3 K1 axis [59].…”
Section: Relationship Between Exosome Content and Pca Mrnamentioning
confidence: 99%
“…In addition, it was reported that exosomal circRNA HIPK3 knockdown inhibited cell proliferation and metastasis in prostate cancer by regulating miR-212/BMI-1 pathway [58]. circ0081234 was inhibited is able to reduce prostate cancer tumor growth and metastasis via the miR-1/ MAP 3 K1 axis [59].…”
Section: Relationship Between Exosome Content and Pca Mrnamentioning
confidence: 99%
“…We showed that PARP1 binds several types of RNAs, but due to the novelty of circRNA detection and the limitations of bioinformatic tools for their discovery, we did not probe for PARP1‐circRNA interactome. However, a recent study showed that circTFDP2 binds directly to the DNA‐binding domain of PARP1, and affecting PARP1's activity (L. Ding et al, 2023).…”
Section: Structural Domains Of Parp1mentioning
confidence: 99%
“…In competition assays, we showed that though PARP1 preferentially binds DNA, deletion of Zn1 and Zn2 DNA binding domains shifted PARP1 from a DNA binder to an RNA binder (Melikishvili et al, 2017). A recent finding however, showed that circTFDP2 binds PARP1 at the DNA binding domain (L. Ding et al, 2023). These results suggest that there could be multiple sites on PARP1 important for PARP1‐RNA and PARP1‐circRNA.…”
Section: Structural Domains Of Parp1mentioning
confidence: 99%
“…Plentiful studies have revealed that circRNAs are implicated in multiple biological processes of tumorigenesis and malignant progression via acting as microRNA (miRNA) sponges, RNA binding protein (RBP) molecules, transcriptional regulators, or templates for protein translations 29–34 . There are currently multiple studies demonstrating that circRNAs, as a major regulator of PCa, can influence the occurrence and progression of PCa in various ways 35–38 . However, the exploration of circRNAs' regulation in cellular senescence of PCa was limited.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34] There are currently multiple studies demonstrating that circRNAs, as a major regulator of PCa, can influence the occurrence and progression of PCa in various ways. [35][36][37][38] However, the exploration of circRNAs' regulation in cellular senescence of PCa was limited.…”
mentioning
confidence: 99%